Spatial dimensions of soil sealing management in growing and shrinking cities – a systemic multi-scale analysis in Germany - Artmann, Martina (ERDKUNDE, 2013)
The paper analyses and evaluates approaches to the management of urban soil sealing to support the implementation of guidelines and sustainability targets, such as the European Commission’s soil sealing guidelines and the sustainability strategy in Germany which aims to reduce the daily land consumption and the associated soil sealing. Based on the assumption that only a mix of instruments can steer soil sealing the paper aims to answer the following questions: I) What are the spatial dimensions of urban soil sealing? II) Which strategies and management dimensions can control soil sealing on a macro-scale (regions, federal states, federal government), meso- (city level) and a micro-scale (urban structural units)? Spatial driving forces of and impacts of soil sealing are identified by urban structural units using a soil sealing gradient. Growing and shrinking cities in Germany were analyzed: Leipzig as a shrinking and Munich as a growing case study city. Results show that neither a growing nor a shrinking population drives the sealing development but the degree of re-use of urban brownfields. Overall, a holistic approach to soil sealing management comprises a multi-dimensional range of measures for the quantitative, qualitative and compensatory management of urban soil sealing and urban green areas, including basically the protection of soils. Economic and fiscal, planning and legal, informational and co-operative strategies have the potential to steer urban soil sealing. Further research is necessary to develop indicators to assess the efficiency of these strategies to achieve a holistic and efficient soil sealing management. This paper presents a framework showing how a set of instruments can be defined and their efficiency assessed by taking into account the identified spatial dimensions and strategies as well as their interconnections.